(untitled) (Research, Society and Development, 2020)
Climatic conditions have a strong influence in the cultivation of the vine. High precipitation and low temperatures, for example, can cause the grapes not reach adequate maturation indexes. In order to check the effect of defoliation and application of abscisic acid (S-ABA) to improve grape quality, an experiment was conducted in a commercial vineyard of ‘Primitivo’ grape, in South of Brazil, for two growing seasons. The treatments were as follows: 1) control; 2) manual defoliation in early maturation (’veraison’); 3) 15 days after the first manual defoliation; 4) abscisic acid 200 mg L-1; 5) abscisic acid 400 mg L-1; 6) abscisic acid 600 mg L-1. The variables soluble solids, titratable acidity, total polyphenols and anthocyanins, color intensity in berries, photosynthetically active radiation, chlorophyll index, percentage of defoliation and chlorosis were evaluated. Manual defoliation held 15 days after the first defoliation increased soluble solids and reduced titratable acidity, while the application of 400 mg L-1 S-ABA increased the titratable acidity of the grape must. There was a higher photosynthetically active radiation near the bunch to defoliation treatments and S-ABA. The application of S-ABA provided chlorosis in leaves, followed by low chlorophyll content, causing the senescence. Hence, defoliation 15 days after first manual defoliation influenced soluble solids and titratable acidity, and application of abscisic acid increased levels of total polyphenols, anthocyanins and color intensity in ‘Primitivo’ berries skins.